(untitled) (Veterinary Science, 2017)
The authors inform the case of horse wich showed a four-month-old of connection/attachment in the proximal median sesamoid bone of the right front/anterior limbo Taking in account de the time that had passed, the scarse limited osteogenic, ability of connective tissue surrounding the sesamoid bone, and the failure of the operation, the implant was removed and the treatrnent was decided with a combination of sodium oleato, mesenchimatous tissue and ficocoiloides monodental, in situ over the interruption. This formula was applied every 72 hs during 3 weeks and then once a week during 6 weeks. At the sometimes abone regenerative was administrated orally. When the applications were finished, the horse was kept at rest for 5 months. After that period, the correction ofthe defect was verifiedusin X rays